Amaranth peptides with antithrombotic activity released by simulated gastrointestinal digestion - Sabbione, Ana Clara (2016)
Amaranth protein isolate was obtained and subjected to simulated gastrointestinal digestion to evaluate its potential antithrombotic activity. The protein isolate did not present fibrin clotting inhibition at the concentrations studied, whereas the hydrolysate (DH% = 51.1 ± 3.8%) exhibited inhibition of fibrin coagulation, showing a dose-response behaviour (IC50 = 0.23 ± 0.02 mg/mL), confirming that the enzymatic treatment was able to release bioactive peptides from amaranth proteins. A fraction with high antithrombotic activity was obtained from this hydrolysate, and resulted to be three times more potent than its original sample (IC50 = 0.07 ± 0.01 mg/mL). The absorption of this active fraction was studied with an in vitro peptides transport assay through intestinal epithelium and it was observed that some peptides are able to cross the Caco2-TC7 cell monolayer. Potentially bioactive peptides were found after sequencing them, and informatics tools allowed us to select and locate in their native molecules those peptides prone to inhibit thrombin activity.